NEW REFERENCE PARAMETERS FOR BODY MASS INDEX IN CHILDREN AGED SIX TO TEN YEARS - Alex Sander Freitas; Marise Fagundes Silveira; José Jorge Francisco de Santana; Marcos Flávio Silveira Vasconcelos D'Ângelo; Desirée Sant'Ana Haikal; Renato Sobral Monteiro-Junior (Sociedade de Pediatria de São Paulo, 2020)
ABSTRACT Objective: To determine new body mass index (BMI) reference values to classify the nutritional status of children aged six to ten years old from the city of Montes Claros (state of Minas Gerais), Southeast Brazil. Methods: The sample consisted of 3,863 individuals from both genders. Body mass and height were measured to determine the BMI. We adopted the Lambda, Mu, and Sigma (LMS) method to obtain the cut-off points. After that, each stratum curve was smoothed using quartic polynomials by gender. Average interpolation was used to determine the biannual distribution values. We calculated the 3rd, 85th, and 95th centiles to classify underweight, overweight, and obesity, respectively, according to gender and age. Results: After tabulating the LMS parameters at biannual intervals by gender, we plotted a graphic with seven centiles of BMI distribution and calculated the new BMI parameters for children aged 6-10 years old from the city of Montes Claros. The cut-off values for underweight, overweight, and obesity classification were, respectively, 17.5, 25 and 30 kg/m2. Conclusions: For the studied children, the use of traditional BMI references may result in the overestimation of underweight and underestimation of overweight and obesity. Studies should be carried out with periodic updates, respecting the characteristics of each location in order to use BMI reference values to classify the nutritional status of children and adolescents.